2016
DOI: 10.2320/matertrans.mh201510
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ternary Ti-25Nb-11Sn Alloy by Powder Metallurgy Route Using Titanium Hydride Powder

Abstract: In the present work, Ti-25Nb-11Sn (mass%) alloys were successfully prepared by an advanced powder metallurgy method. The alloys were synthesized by mechanical milling of powder mixture, consisting of titanium hydride (TiH 2 ), elemental niobium (Nb) and elemental tin (Sn) powders, followed by their consolidation via Spark Plasma Sintering (SPS) method. The use of brittle TiH 2 powder, instead of ductile elemental Ti powder, resulted in ~100% powder yield of mechanically milled (MMed) powder even after long tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…In the literature, the feasibility of the mechanical properties for orthopedic implants of porous Ti-Nb-Sn alloys has been demonstrated [29][30][31][32][33][34][35]. The Ti-Nb-Sn system is a nontoxic alternative with low-elastic moduli for medical implants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, the feasibility of the mechanical properties for orthopedic implants of porous Ti-Nb-Sn alloys has been demonstrated [29][30][31][32][33][34][35]. The Ti-Nb-Sn system is a nontoxic alternative with low-elastic moduli for medical implants.…”
Section: Introductionmentioning
confidence: 99%
“…The high strength and low elastic modulus achieved in Ti-Nb-Sn alloys is related to the occurrence of stress-induced martensitic transformation and its reverse transformation [33]. The addition of Nb and Sn decreases the maximum martensitic transformation strain [32]. For the present study, 34 and 6 wt.% of Nb and Sn were chosen to promote the stabilization of β phase, respectively [36].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sharma et al. [ 92 ] reported that TiH 2 with a small particle size and a larger surface area could achieve a higher hydrogen decomposition percentage. Mechanical milling was used to create Ti-25-Nb-11Sn alloy from TiH 2 , Nb, and Sn, which was then consolidated using Spark Plasma Sintering (SPS) at two different milling times (72 ks and 180 ks).…”
Section: Dehydrogenation Processmentioning
confidence: 93%
“…Moreover, the use of extremely brittle TiH 2 powder, instead of highly ductile pure titanium powder, can overcome the sticking/agglomeration issues as well as contamination-related issues by avoiding process control agents (PCAs) in the mechanical milling process. As a result, a uniform distribution of elemental powders with an almost complete powder yield can be ensured even a long time after mechanical alloying [21][22][23]. It has also been reported that various properties, such as grain refinement, improvement in superplastic forming and reduction in the flow stress, can be improved through temporary hydrogen alloying [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%